2019
DOI: 10.1111/jdv.15884
|View full text |Cite
|
Sign up to set email alerts
|

Key characteristics of basal cell carcinoma with large subclinical extension

Abstract: Background Basal cell carcinoma with large subclinical extension (BCC‐LSE) is a tumour whose extensive spread becomes apparent during Mohs surgery histopathology review. Not recognizing BCC‐LSE preoperatively may result in a greater number of Mohs layers and in larger than anticipated postoperative defects. Objective To evaluate the characteristics of BCC‐LSE. Methods This retrospective study reviewed BCC treated with Mohs surgery at a single academic surgical centre between March 2007 and February 2012. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…Regarding high-risk location, there is a statistically significant difference in a number of stages between tumors located in the periocular region and tumors of the ear, nose, or perioral area, with periocular BCCs requiring more stages of surgery. Although location on high-risk areas was shown to be associated with a higher number of stages in previous studies, 4 , 5 , 7 the specification and comparison between various high-risk areas are more rarely mentioned in the literature.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Regarding high-risk location, there is a statistically significant difference in a number of stages between tumors located in the periocular region and tumors of the ear, nose, or perioral area, with periocular BCCs requiring more stages of surgery. Although location on high-risk areas was shown to be associated with a higher number of stages in previous studies, 4 , 5 , 7 the specification and comparison between various high-risk areas are more rarely mentioned in the literature.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown that both tumor and patient characteristics may predict a higher number of stages necessary to achieve clear margins. 4 , 5 Aggressive histological subtypes such as micronodular, infiltrative, and morphea form are well-known factors for a higher number of stages and larger clearance margins. 6 In a very recent study, Cerci et al concluded that not just micronodular, infiltrative, and morphea form histological subtypes were associated with larger margins but also superficial ones (due to greater subclinical extension); whereas clinically well-defined and small tumors needed smaller margins, with tumors < 6 mm having a clearance rate of 96% with 3-mm margins; preoperative tumor size was a significant predictor of larger margins and number of MMS stages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among Caucasians, the cases that require ≥ 3 rounds of Mohs surgery are classified under extensive subclinical spread 14) . This holds true for our patient as well.…”
Section: Discussionmentioning
confidence: 99%
“…This holds true for our patient as well. The previously reported characteristics for patients with a marked subclinical extension include: 1) elderly males; 2) Fitzpatrick skin type I; and 3) a history of BCC of the following types -basosquamous, metatypical, micronodular, infiltrative, morpheaform, and sclerosing type 14) . In the case reported herein, the BCC was micronodular, which is an aggressive form of tumor; however, The basal cell carcinoma existed in the region marked with red.…”
Section: Discussionmentioning
confidence: 99%